2008
DOI: 10.1007/s00040-008-0983-8
|View full text |Cite
|
Sign up to set email alerts
|

Argentine ant infestation affects the abundance of the native myrmecophagic jumping spider Siler cupreus Simon in Japan

Abstract: The effect of an Argentine ant invasion on the abundance of the myrmecophagic jumping spider Siler cupreus Simon was investigated in the Hiroshima Prefecture, southwestern Japan. The frequency and density of S. cupreus were significantly higher in sites infested with Argentine ants than in ant-free sites. S. cupreus actually preyed on the adult ants and the brood. The dominance of Argentine ants possibly provides an abundant food source for S. cupreus, thus causing an increase in the number of spiders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…To date, Argentine ant invasions had only been found to reduce predator abundance in the case of the coastal horned lizard, P. coronatum, a highly specialized predator of ants (Suarez et al 2000;Fisher et al 2002). In contrast, other ant specialists seem to have benefitted from the abundant food that stems from Argentine ant invasions (Touyama et al 2008;Glenn and Holway 2008). In this study, we found differential effects of the invasion on adult amphibian abundance, which could be related to the species' degree of dietary specialization.…”
Section: Effects On the Amphibian Communitymentioning
confidence: 54%
See 2 more Smart Citations
“…To date, Argentine ant invasions had only been found to reduce predator abundance in the case of the coastal horned lizard, P. coronatum, a highly specialized predator of ants (Suarez et al 2000;Fisher et al 2002). In contrast, other ant specialists seem to have benefitted from the abundant food that stems from Argentine ant invasions (Touyama et al 2008;Glenn and Holway 2008). In this study, we found differential effects of the invasion on adult amphibian abundance, which could be related to the species' degree of dietary specialization.…”
Section: Effects On the Amphibian Communitymentioning
confidence: 54%
“…Once the Argentine ant has established itself, it displaces almost all native ant species (Suarez et al 1998;Carpintero et al 2005;Holway and Suarez 2006;Angulo et al 2011). Its effects on non-ant species, including ant specialist predators, have been studied in California and Japan (e.g., Suarez and Case 2002;Touyama et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O comportamento de predação denominado "snatching" (JAckson et al 2008), embora seja um dos mais raros, destaca-se como um dos mais complexos: Exibindo esse padrão de comportamento, as aranhas interagem com formigas forrageadoras roubando as presas transportadas em suas mandíbulas. Espécimes imaturos que estejam sendo transportados também podem ser roubados e consumidos (touyAmA et al 2008).…”
Section: _____________________________________unclassified
“…; Touyama et al . ). To date, no studies have been undertaken on the effects of the Argentine ant on myrmecophilous species living inside nests of native ants.…”
mentioning
confidence: 97%